2010
DOI: 10.2109/jcersj2.118.1150
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and tribological characterization of gradient carbon layer derived from SiC-TiC composites

Abstract: Carbide based ceramics are frequently used for the tribological applications, such as mechanical seals, owing to their good mechanical and chemical properties. Recently, studies of the tribological properties of these applications have become increasingly important due to the increasing need for severe operating conditions. In this study, the surface modification of carbide ceramics was attempted to improve the triblogical properties. Carbon layers were prepared on SiCTiC ceramics using a moderate and high tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In addition, the tribological properties of CDC films can be improved by modifying the film surface with a gradient carbon layer fabricated using SiC and TiC composites. 35) The Ti and Si components are etched at lower and higher temperatures, respectively, since TiC and SiC are chlorinated at 600 and 1000°C, respectively. Therefore, a carbon film consisting of a mixture of carbon and SiC grains is formed as a gradient layer, depending on the TiC and SiC compositions and the reaction time at each reaction temperature.…”
Section: Effect Of Gradient Carbon Layermentioning
confidence: 99%
“…In addition, the tribological properties of CDC films can be improved by modifying the film surface with a gradient carbon layer fabricated using SiC and TiC composites. 35) The Ti and Si components are etched at lower and higher temperatures, respectively, since TiC and SiC are chlorinated at 600 and 1000°C, respectively. Therefore, a carbon film consisting of a mixture of carbon and SiC grains is formed as a gradient layer, depending on the TiC and SiC compositions and the reaction time at each reaction temperature.…”
Section: Effect Of Gradient Carbon Layermentioning
confidence: 99%
“…Despite the characteristics of low friction and high wear resistance, the tribological properties of CDC coatings should be improved to use under extreme conditions [7][8][9][10][11][12]. Carroll et al demonstrated that CDC coatings with an onion-like structure exhibited low friction in dry nitrogen [10].…”
Section: Introductionmentioning
confidence: 99%
“…McNallan et al reported that the friction coefficient of CDC coatings was significantly reduced by hydrogen post-treatment [11]. Additionally, the tribological behavior of CDC coatings was modified by a gradient SiC/C structure and optimized by controlling the residual SiC grain content [12]. These methods mainly focused on the optimization of the processing parameters for CDC coatings.…”
Section: Introductionmentioning
confidence: 99%